Epstein-Barr Virus and the Pathogenesis of Diffuse Large B-Cell Lymphoma - Ross, Aisling M; Leahy, Ciara I; Neylon, Fiona; Steigerova, Jana; Flodr, Patrik; Navratilova, Martina; Urbankova, Helena; Vrzalikova, Katerina; Mundo, Lucia; Lazzi, Stefano; Leoncini, Lorenzo; Pugh, Matthew; et al. (Life, 2023)
Epstein-Barr virus (EBV), defined as a group I carcinogen by the World Health Organization (WHO), is present in the tumour cells of patients with different forms of B-cell lymphoma, including Burkitt lymphoma, Hodgkin lymphoma, post-transplant lymphoproliferative disorders, and, most recently, diffuse large B-cell lymphoma (DLBCL). Understanding how EBV contributes to the development of these different types of B-cell lymphoma has not only provided fundamental insights into the underlying mechanisms of viral oncogenesis, but has also highlighted potential new therapeutic opportunities. In this review, we describe the effects of EBV infection in normal B-cells and we address the germinal centre model of infection and how this can lead to lymphoma in some instances. We then explore the recent reclassification of EBV+ DLBCL as an established entity in the WHO fifth edition and ICC 2022 classifications, emphasising the unique nature of this entity. To that end, we also explore the unique genetic background of this entity and briefly discuss the potential role of the tumour microenvironment in lymphomagenesis and disease progression. Despite the recent progress in elucidating the mechanisms of this malignancy, much work remains to be done to improve patient stratification, treatment strategies, and outcomes.